Intelectual discourse: Experience of group of PhD student and their supervisor - Dali, Mohd Hasani; Elliot, John; Lam, John; Lau, Grace; Lo, Brenda; Meakin, Martin; Rudge, Linda; Sallnow, Anna (UUM Press, 2006)
This paper takes the form of a conversation between a group of seven doctoral students and their supervisor Profesor John Elliott of the Centre for Applied Research in Education (CARE) at the University of East Anglia, United Kingdom. It was constructed through three rounds of e-mail exchanges between May and September 2004 and focuses on methodological issues surrounding the conduct of applied educational research for the purpose of producing a doctoral thesis.